Application of soil flocculation in removal of toxic alexandrium minutum and protoceratium reticulatum (Dinophyceae) - Tang, Clare Siing Nga (Universiti Malaysia Sarawak, (UNIMAS), 2011)
Aquacultures industries in Malaysia suffered great losses in recent year due to the occurrence of harmful algal blooms (HABs), partly due to absent of mitigation strategies in dealing with these events. Clay flocculation has been known to effective in HABs mitigation and widely applied in East Asian countries. However, efficiency of this mitigation method differed due to the properties of soil material. The objective of this study was to assess the efficiency of two local soils in removal of several known harmful dinoflagellates, i.e. Alexandrium minutum and Protoceratium reticulatum. Both soil samples used in this study composed mainly clay (45-68%), followed by sand (15-22%) and silt (17-33%). Removal efficiency increased significantly (p < 0.05) with higher clay concentration, but differed in the two species and soils tested. Soil sample B showed high efficiency in removal of A. minutum cells with total removal (Bmax ~ 100%) achieved at concentration as low as 0.2 g. For P. reticulatum, maximum removal of cells by both soils was achieved within 2 h. This study clearly showed the potential of local soils in mitigation of HABs. Field trial of clay dispersal during the blooms event is essential to verify the outcome of this study.